Menjadi Pribadi yang Memberi Manfaat: Edukasi Karakter bagi Remaja dan Masyarakat - Yusutria Yusutria; Rina Febriana (Gemi: Jurnal Penelitian dan Pengabdian, 2026)
The community service program "Becoming a Beneficial Person: Character Education for Youth and Society" was implemented to address the declining public understanding of the purpose of life, which is oriented towards the value of usefulness. Modernization, individualism, and the influence of technology have caused adolescents and adults to increasingly distance themselves from the values ​​of caring, empathy, and social responsibility. This community service activity was conducted at the Al-Amanah Mosque in Pilahan, Rejowinangun, Kotagede, using an educational, participatory, and empowerment approach. Implementation methods included interactive lectures, group discussions, consultations, self-reflection, and the formulation of commitments to action. Evaluation was conducted through observation and pre- and post-test questionnaires. The results of the activity showed a significant increase in participants' understanding of the essence of life's purpose; 100% of participants reaffirmed their understanding of the importance of being a beneficial person. Furthermore, 57% of participants acknowledged challenges in behavioral consistency, but all demonstrated a strong commitment to change and contribute positively to their social environment. This activity proved effective in building awareness, strengthening motivation, and revitalizing the mosque's role as a center for character education. This program has the potential to be developed through further mentoring, community collaboration, and the provision of more systematic character education modules.